2018
DOI: 10.13031/trans.12801
|View full text |Cite
|
Sign up to set email alerts
|

Use of CSM-CROPGRO-Cotton to Determine the Agronomic and Economic Value of Irrigation to Upland Cotton Production in North and South Carolina

Abstract: Abstract. Although prior research has shown that irrigation can increase cotton fiber yields in coastal plain soils of the Carolinas, only 2.7% of North Carolina’s and 7.8% of South Carolina’s planted hectares are irrigated, compared to 39% nationally. Little research has addressed the impact of compacted subsurface soil layers on the value of irrigation. Economic analysis of irrigation is also difficult due to the lack of long-term irrigation data for the region. The objectives of this study were to adapt the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The DSSAT CSM can simulate crop growth, development, and yield in response to variability in weather conditions, soil properties, and management practices (Jones et al, 2003;Hoogenboom et al, 2012Hoogenboom et al, , 2015Thorp et al, 2014). The DSSAT CSM CROPGRO-Cotton model has been extensively used by researchers worldwide for various applications (Buttar et al, 2007;Pathak et al, 2007;Ortiz et al, 2009;Pereira et al, 2009;Thorp et al, 2010Thorp et al, , 2014Modala et al, 2015;Adhikari et al, 2016Adhikari et al, , 2017Mauget et al, 2017;Loison et al, 2017;Amin et al, 2018;Spivey et al, 2018).…”
mentioning
confidence: 99%
“…The DSSAT CSM can simulate crop growth, development, and yield in response to variability in weather conditions, soil properties, and management practices (Jones et al, 2003;Hoogenboom et al, 2012Hoogenboom et al, , 2015Thorp et al, 2014). The DSSAT CSM CROPGRO-Cotton model has been extensively used by researchers worldwide for various applications (Buttar et al, 2007;Pathak et al, 2007;Ortiz et al, 2009;Pereira et al, 2009;Thorp et al, 2010Thorp et al, , 2014Modala et al, 2015;Adhikari et al, 2016Adhikari et al, , 2017Mauget et al, 2017;Loison et al, 2017;Amin et al, 2018;Spivey et al, 2018).…”
mentioning
confidence: 99%
“…Puntel et al [19] reported that the Agricultural Production Systems sIMulator (APSIM) effectively simulated (S) the long-term effects of different nitrogen rates on corn yield and winter wheat-summer maize yields in central Iowa, USA. Examples of others are given by Zhao et al [20], Li et al [21], Lu et al [22], Kothari et al [23], Marek et al [24], Masasi et al [25], Mompremier et al [26], Attia et al [27] and Spivey et al [28]. Long-term simulations of agricultural management strategies on crop yield are mainly concentrated in semi-arid and arid regions.…”
Section: Introductionmentioning
confidence: 99%